REDOX STATE OF EARTH'S UPPER MANTLE PERIDOTITES UNDER THE ANCIENT CRATONS AND ITS CONNECTION WITH DIAMOND GENESIS - Simakov S.K. (My University, 1998)
P-T-fO2 conditions and fluid compositions were estimated from mineral paragenesis from inclusions in diamonds, diamond-bearing, and diamond-free xenoliths using garnet-orthopyroxene barometers and olivine-orthopyroxene-garnet oxygen barometer. The data indicate that upper mantle is zoned, with relatively oxidized lithosphere and reduced astenosphere. The upper mantle becomes increasingly reduced with increasing depth. Inclusions within diamonds could have formed in equilibrium with the methane-nitrogen-rich fluids which corresponded to the existence of metal-silicate melts. Diamond-bearing and diamond-free peridotite xenoliths equilibrated with CO2-H2O and CO2-rich fluids correspondingly.